'Mind your Moles' study: protocol of a prospective cohort study of melanocytic naevi. Issue 9 (19th September 2018) - Koh, Uyen; Janda, Monika; Aitken, Joanne F; Duffy, David L; Menzies, Scott; Sturm, Richard A; Schaider, Helmut; Betz-Stablein, Brigid; Prow, Tarl; Soyer, H Peter; Green, Adele C
Abstract : Introduction: Having many melanocytic naevi or 'moles' on the skin is the strongest predictor of melanoma; thus, much can be learnt from investigating naevi in the general population. We aim to improve the understanding of the epidemiology and biology of naevi by conducting a 3-year prospective study of melanocytic naevi in adults. Methods and analysis: This is a population-based cohort study of melanocytic naevi in 200 adults aged 20–69 years recruited via the Australian electoral roll. At baseline, participants will complete a questionnaire on their sun behaviour and health and undergo a clinical examination. Three-dimensional (3D) total-body photography will be used to record the images of skin lesions. Pigmented naevi will be analysed in terms of number, diameter, colour and border irregularity using automated analysis software (excluding scalp, beneath underwear and soles of feet). All naevi ≥5 mm will be recorded using the integrated dermoscopy photographic system. A saliva sample will be obtained at baseline for genomic DNA analysis of pigmentation, naevus and melanoma-associated genes using the Illumina HumanCoreExome platform. The sun behaviour and health follow-up questionnaire, clinical examination and 3D total-body photography will be repeated every 6 months for 3 years. The first 50 participants will also undergo manual counts of naevi ≥2 mm and ≥5 mm at baseline, 6-month and 12-month follow-ups. Microbiopsy and excision of naevi of research interest is planned to commence at the 18-month time point among those who agree to donate samples for detailed histopathological and molecular assessment. Ethics and dissemination: This study was approved by the Metro South Health Human Research Ethics Committee in April 2016 (approval number: HREC/16/QPAH/125). The findings will be disseminated through peer-reviewed and non-peer-reviewed publications and presentations at conferences.